Chronic hypoxia has differential effects on constitutive and antigen-stimulated immune function in Atlantic salmon (Salmo salar) - Rojas, Isis; de Mello, Mariana M. M.; Zanuzzo, Fábio S.; Sandrelli, Rebeccah M.; Peroni, Ellen de Fátima C.; Hall, Jennifer R.; Rise, Matthew L.; Urbinati, Elisabeth C.; Gamperl, Anthony K. (Frontiers in Immunology, 2025)
Chronic hypoxia events are a common occurrence in Atlantic salmon (Salmo salar) sea-cages, especially during the summer, and their frequency and severity are predicted to increase with climate change. Although hypoxia is considered a very important fish health and welfare issue by the aquaculture industry, few studies have investigated the impact of chronic hypoxia on the fish immune system and its response to pathogen exposure. We exposed post-smolt Atlantic salmon to hypoxia (40% air sat.) for 6 weeks. Thereafter, we sampled fish prior to (i.e., at Time 0, to assess constitutive immune function), and after they were intraperitoneally injected with PBS (phosphate buffered saline) or formalin-killed Aeromonas salmonicida. We measured several innate immune parameters including: hematological immune responses [respiratory burst (RB), hemolytic activity of alternate complement system and plasma lysozyme concentration], and the relative percentage of circulating blood cells (erythrocytes/immature erythrocytes, monocytes, and granulocytes and lymphocytes) at Time 0 and at 24 hours post-injection (hpi); and the transcript expression levels of 8 anti-bacterial biomarkers in the head kidney [interleukin-1 beta (il1b), interleukin-8a (il8a), cyclooxygenase-2 (cox2), toll-like receptor 5, secreted (strl5), CC chemokine-like 19b (ccl19b), serum amyloid A5 (saa5), hepcidin anti-microbial peptide a (hampa) and cathelicidin anti-microbial peptide b (campb)] at Time 0 and at 6 and 24 hpi. In addition, we measured serum immunoglobulin (IgM) levels at Time 0 and at 8 weeks post-injection (4 weeks after a ‘boost’ injection). Fish exposed to chronic hypoxia had greater numbers of monocytes, which was consistent with the increase in RB, plasma lysozyme concentration and upregulated head kidney anti-bacterial gene expression (i.e., campb, ccl19b, hampa, il8a, stlr5). In contrast, chronic hypoxia: reduced RB and leukocyte numbers at 24 hpi in Asal compared to PBS-injected fish, and the transcript levels of campb, il1b, saa5, il8a and stlr5 at 6- and/or 24- hpi; but had no effect on constitutive or post-stimulation serum IgM titers. Overall, our results indicate that chronic hypoxia has differential effects on salmon constitutive innate immune function vs. following antigen exposure, and thus, it is still unclear how chronic hypoxia will impact the capacity of fish to defend against pathogens.